Prevalence of preoperative anxiety among Hausa patients undergoing elective surgery- a descriptive study - Dagona, Sabo Saleh (Advances in Social Sciences Research Journal, 2018)
The aim of this study is to assess the prevalence of preoperative anxiety among Nigerian Hausa patients undergoing elective surgery. Methods: Thirty patients between the ages of 17- 64 years scheduled to undergo elective surgery in a tertiary health facility in northern Nigeria were recruited and administered a translated Hausa version of the Amsterdam Preoperative Anxiety and Information Scale (APAIS-H).APAIS-H was administered to each patient in the evening before and in the morning of their surgery day. Results: Statistical Package for Social Sciences (SPSS) Version 23.0 was used to analyze the data. Analyses were according to the APAIS subscales to see preoperative anxiety a day before and on the day of surgery. On both the fear of anesthesia and fear of surgery subscales, 76.6% of the participants presented with low to moderate anxiety in the evening proceeding the day of their surgery. Only 23.3% of the participants were highly anxious about either anesthesia or surgery in the evening proceeding the day of their surgery. On the anxiety related to surgery subscale, in the morning of the surgery day, 36.7% of the participants had low to moderate anxiety related to anesthesia while 63.3% were highly anxious about anesthesia. Also, 40% of the participants presented with low to moderate anxiety related to surgery in the morning of their surgery while the remaining 60% were highly anxious about the surgery in the morning of the day of their surgery. The full-scale preoperative anxiety scores reveal that 53% of the participants had low anxiety, 26.7 had moderate anxiety while 20% of participants had high preoperative anxiety in the evening preceding their surgery. In the morning of the day of their scheduled surgery, 20% of the participants presented with low anxiety, another 20% had moderate anxiety while the remaining 60% had high preoperative anxiety. Conclusion: The findings of the study show that anxiety before elective surgery is prevalent among Hausa patients. It is therefore recommended that adequate psychological preoperative anxiety reduction interventions be put in place to address patients’ anxiety to achieve a better surgical outcome.